Prevalência e fatores associados à sífilis gestacional no contexto da pandemia de COVID-19 - Lopes, Wanda Carvalho (2025)
INTRODUCTION: The COVID-19 pandemic negatively impacted prenatal, childbirth, and postpartum care, resulting in changes in hospital protocols and an increase in gestational syphilis cases due to reduced access to prenatal care. OBJECTIVE: To analyze the prevalence of gestational syphilis and factors associated with it in the context of the COVID-19 pandemic. METHODOLOGY: This cross-sectional study was carried out in a referral hospital in central Brazil, using secondary data from pregnant women’s medical records and systems such as SPDATA, MV, and SINAN NET. Cases of gestational syphilis diagnosed between 2018 and 2022, corresponding to the pre-pandemic and pandemic periods of COVID-19, were analyzed. The dependent variable was the prevalence of gestational syphilis, diagnosed clinically and through treponemal and non-treponemal serological tests. The independent variables included the COVID-19 pandemic, sociodemographic factors, access to healthcare services, and maternal and obstetric factors. RESULTS: The study revealed that 62.2% of the pregnant women did not have a paid job and 55.6% were without a partner. In addition, 16.5% had not undergone prenatal care and 54.8% had six or fewer appointments. HIV coinfection was observed in 3.1% of the pregnant women, and 51% reported previous pregnancies, with an abortion rate of 16.1%. The prevalence of gestational syphilis increased from 0.80% in the pre-pandemic period to 1.67% during the pandemic, representing a 108.75% increase. During the pandemic, there was a significant decrease in the number of normal births (p = 0.035; Exp(B) = 0.8; 95% CI: 0.69 - 0.99). HIV prevalence was higher in the pre-pandemic period, with a 153% higher risk for pregnant women in this period (p = 0.009; Exp(B) = 2.5; 95% CI: 1.26 - 5.00). Pregnant women with syphilis in the pre-pandemic period were significantly less likely to have a paid job (p = 0.038; Exp(B) = 0.83; 95% CI: 0.71 - 0.99). There were significant differences between the groups in terms of mode of delivery (p=0.012) and abortion rate (p=0.016). CONCLUSIONS: The study found a higher prevalence of gestational syphilis during the pandemic, with significant differences between the groups in terms of mode of delivery and abortion rate, highlighting the negative impact of syphilis on obstetric outcomes.